Cardiovascular Risk Factors Increase the Risks of Diabetic Peripheral Neuropathy in Patients With Type 2 Diabetes Mellitus: The Taiwan Diabetes Study. Issue 42 (October 2015) - Yang, Chun-Pai; Lin, Cheng-Chieh; Li, Chia-Ing; Liu, Chiu-Shong; Lin, Wen-Yuan; Hwang, Kai-Lin; Yang, Sing-Yu; Chen, Hsuan-Ju; Li, Tsai-Chung
Abstract : Abstract: This study aimed to examine whether poor glycemic control, measured by glycated hemoglobin A1C (HbA1c) and other cardiovascular risk factors, can predict diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes mellitus (DM). Patients aged ≥30 years with type 2 DM, enrolled in the National Diabetes Care Management Program, and free of DPN (n = 37, 375) in the period 2002 to 2004 were included and followed up until 2011. The related factors were analyzed using Cox proportional hazards regression models. For an average follow-up of 7.00 years, 8379 cases of DPN were identified, with a crude incidence rate of 32.04/1000 person-years. After multivariate adjustment, patients with HbA1c levels 7 to 8%, 8 to 9%, 9 to 10%, and ≥10% exhibited higher risk of DPN (adjusted HR: 1.11 [1.04–1.20], 1.30 [1.21–1.40], 1.32 [1.22–1.43], and 1.62 [1.51–1.74], respectively) compared with patients with HbA1c level 6 to 7%. There was a significant linear trend in DPN incidence with increasing HbA1c ( P < 0.001) and significant HRs of DPN for patients with HbA1c level ≥7%, blood pressure ≥130/85 mm Hg, triglycerides (TG) ≥150 mg/dL, high density of lipoprotein-cholesterol (HDL-C) <40 mg/dL in males and <50 mg/dL in females, low density of lipoprotein-cholesterol (LDL-C) ≥100 mg/dL, and estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 . Patients with type 2 DM and HbA1c ≥7.0% exhibit increased risk of DPN, demonstrating a linear relationship. The incidence of DPN is also associated with poor glucose control and cardiovascular risk factors like hypertension, hyper-triglyceridemia, low HDL-C, high LDL-C, and decreased eGFR.